Features of the light-colored structure of the composition of plants - Taran, Nataliya; Dragomyryk, Valeriya (Theory and practice of design, 2022)
Purpose: to investigate the peculiarities of plant compositions at dusk and at night; choose relatively unpretentious plants that are best suited for the current season and briefly describe their features; determine the problems of building such compositions that will look good even in the dark; familiarize yourself with the problems of “night” landscaping and their solutions; research plants that should be emphasized in such landscaping; to determine methods of creating aesthetic plant compositions for twilight using specific examples. Methodology: The article uses comparative and historical analysis. In the course of writing the article, various scientific sources, scientific literature, plant care manuals, photographs, images of plants were used. The results. It was found that the light and color environment is formed on the basis of complex design. This process includes three levels: the formation of artistic impressions from the light-colored environment, the creation of emotional and figurative characteristics and properties; development of engineering devices and light-technical equipment with different operational characteristics; formation of one’s own state of light and color environment for a certain effect on a person, ensuring visual comfort. The need to master the art of lighting, which is decided by architects and designers at the stage of designing the city and the urban environment, has been identified. Scientific novelty: it was found out and established about the existence of certain methods of “night” landscaping, namely: plants that open in the evening; plants that are clearly visible even in the dark; which plants should be highlighted in the dark; the problem of the aesthetic appearance of plant compositions at dusk and in the dark and the solution to this problem; correct lighting of compositions to achieve a greater effect.